2021
DOI: 10.1002/phar.2517
|View full text |Cite
|
Sign up to set email alerts
|

Comparative treatment effectiveness of oral fingolimod and conventional injectable disease‐modifying agents in multiple sclerosis

Abstract: Study Objective To compare the effectiveness of oral fingolimod and conventional injectable disease‐modifying agents (DMAs) using the composite endpoint of relapse or DMA treatment switch in patients with multiple sclerosis (MS). Design A retrospective longitudinal cohort study. Data Source IBM MarketScan Commercial Claims and Encounters Database from 2010–2012. Patients Adults (≥18 years) with MS diagnosis (ICD‐9‐CM:340) who newly initiated DMAs. Intervention Oral fingolimod and conventional injectable DMAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The findings from our study were generally consistent with the limited available literature on trends in DMT use for MS. A 2021 article comparing new use of fingolimod with platform injectable DMTs among commercially insured US adults at least 18 years found that, between 2010 and 2011, platform injectables accounted for 84.4% of new use episodes, while fingolimod accounted for 15.6% . Our study found similar results for 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our study were generally consistent with the limited available literature on trends in DMT use for MS. A 2021 article comparing new use of fingolimod with platform injectable DMTs among commercially insured US adults at least 18 years found that, between 2010 and 2011, platform injectables accounted for 84.4% of new use episodes, while fingolimod accounted for 15.6% . Our study found similar results for 2011.…”
Section: Discussionmentioning
confidence: 99%